Handling waste through consensus, care and community in Auckland, Aotearoa New Zealand. - Fischer, Jeannine-Madeleine (Routledge, 2021)
Eco-friendly initiatives play an important role in Auckland, the biggest city of a country that performs globally as “clean and green” and publicly strives to become “the world’s most livable city” (Auckland Council 2012). Based on ethnographic research, this chapter shows how a consensus about environmental care interrelates with urban governance. Creating not only eco-friendly but also responsible and active subjects, environmental care can be aligned with a neoliberal framework. In this chapter I refer to a community waste reduction initiative and argue that caring for waste interrelates with caring for the community. Taking shape in forms of “intimate governance” (Agrawal 2005), local processes of power and representation are being reinforced.
Keywords: Kommunaler Umweltschutz; Urban Governance; Abfallvermeidung; Eigenverantwortung; Ethik; Liberalismus; Gemeinschaftsprojekt; Bürgerinitiative; Kampagne